Relevance of 3D simulations and sandwich core topology for the modeling of honeycomb core sandwich panels undergoing interfacial crack propagation. (15th October 2018) - Höwer, Daniel; Jois, Kumar C.; Lerch, Bradley A.; Bednarcyk, Brett A.; Pineda, Evan J.; Reese, Stefanie; Simon, Jaan-Willem
Abstract: A recently developed cohesive zone traction-separation law, which includes the effects of fiber bridging in a novel way, is extended from 2D to 3D. The proposed cohesive model is applied to low fidelity (i.e. homogenized core representation) and high fidelity (i.e. directly accounting for the core topology) finite element models of a composite panel comprised of carbon fiber reinforced plastic facesheets and a honeycomb sandwich core. This enables the investigation of width-dependent effects such as 1.) the stress concentrations at the specimen edges, 2.) the stress concentrations due to the honeycomb core topology, 3.) the thumbnail-shaped crack growth, and 4.) the conditions under which the honeycomb core topology causes discontinuous crack propagation, which in turn begets oscillations of the global load-displacement curve. To this end, a cohesive parameter transfer procedure from 2D to 3D (low and high fidelity) is developed. Normal stresses of the 3D high and low fidelity predictions are qualitatively similar, whereas shear stresses in the sandwich core are significantly higher and very localized in the 3D high fidelity model. Crack propagation becomes noticeably unstable and global load-displacement curve oscillations occur for certain core topologies. The numerical predictions are compared to experimental load-displacement and R-curves.